Implementasi Program M-Desa Dangin Puri Kangin dalam Peningkatan Pelayanan Administrasi Desa Sadar Jaminan Sosial di Desa Dangin Puri Kangin, Kecamatan Denpasar Utara - Susanti, Made Widya; Winaya, I Ketut; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2019)
ABSTRACT M-Desa Dangri Kangin program is a form of innovation program runs by the head village of Dangin Puri Kangin using technology as the tool to accelerate the services. This program has several service and one of them is BPJS for Employment Service to give the assurance for the community, and improving village administrative services of the awareness of social assurance in Dangin Puri Kangin village. The theory is used to support this research it is proposed by George C. Edward III about Policy Implementation with indicator of communication, resources, disposition, and bureaucratic structure. The descriptive qualitative methods were applied in this research. The result of implementation in M-Desa program is pretty good but in BPJS of Employment Service, some problems still haven’t been solved. It is not running optimally in some other indicators such as communication, the lack of resources, and the absence of SOPs and work unit fragmentation. Keywords: Implementation, Sosical Assurance, E-Government